Uji Aktivitas Antibakteri Ekstrak Etanol Daun Seledri (Apium Graveolens L.) Terhadap Staphylococcus Aureus - Kony Putriani; Nadya Putri Auliya Serawaidi; Asiska Permata Dewi; Maya Radista (LPPM Universitas Abdurrab, 2023)
The use of celery leaves in this study is because celery leaves contain antibacterial compounds such as saponins, tannins, and flavonoids. The aim of this study was to determine the antibacterial activity of the ethanol extract of celery leaves against Staphylococcus Aureus at concentrations of 10%, 30%, and 50% using the agar diffusion method, with chloramphenicol as a positive control and Aquadest as a negative control. The extraction method was carried out by maceration method using 96% ethanol solvent. Inhibition test results with concentrations of 10%, 30%, and 50% of celery leaf ethanol extract could inhibit the growth of Staphylococcus Aureus with an average diameter of the inhibition zone of 0 mm, 0.6 mm, and 10.6 mm. From the above results, the ethanol extract of celery leaves has antibacterial activity with weak activity against Staphylococcus Aureus.